POLY(3)HYDROXYBUTYRATE (PHB) PRODUCTION IN BACILLUS THURINGIENSIS IAM 12077 UNDER VARIED NUTRIENT LIMITING CONDITIONS AND MOLECULAR DETECTION OF CLASS IV PHA SYNTHASE GENE BY PCR. - VAISHNAVI GOWDA; SRIVIDYA SHIVAKUMAR (International Journal of Pharma and Bio Sciences, 2013)
Limiting nutrient in the culture conditions is crucial for PHA production. In this study, B. thuringiensis IAM 12077 was grown in different culture conditions with limitation of potassium, nitrogen, sulphur and phosphorous. In all the limiting conditions used, a similar range of PHAs were produced with glucose as carbon source (10g/L). The PHA yields and accumulation obtained were found to be 1.61g/L, 65.9%; 1.86g/L, 64.1%; 1.66g/L, 65.9% and 1.7g/L, 68.9% dry cell weight (DCW) for potassium, nitrogen, sulphur and phosphorus limitations, respectively, showing that any of the above deficiency can trigger PHB production in this strain. Time course study in N2 deficient medium revealed that though cell biomass remained almost steady from 0h after transfer to production medium till the end of fermentation (120h), PHB yield showed increase from 0.533 g/L at 0h to 4g/L by 48h and later gradually decreased, with PHB accumulation increase from 11% to 77% by 96h. PCR identified the presence of class IV pha synthase in B.thuringiensis IAM12077 suggesting the capability of this strain to accumulate different PHA monomers from structurally unrelated carbon sources which can be explored further.